Genetics and Scientific Values - te Nijenhuis, Jan (The Hastings Center report, 2025)
This letter responds to the essay “Confronting the ‘Weaponization’ of Genetics by Racists Online and Elsewhere,” by Aaron Panofsky, Kushan Dasgupta, Nicole Iturriaga, and Bernard Koch, in “Envisioning a More Just Genomics,” the November-December 2024 special report of the Hastings Center Report.